'Respons'ible Service Quality. Issue 4 (20th August 2014) - Sahai, Vickram; Jain, Arvind Kumar
Abstract : Purpose: A model of Service quality is SERVQUAL, which measures the discrepancy between customer's perceptions and expectation on the customer service. The dimensions of service quality here are evaluated from the customer's point of view. Functional Fluency as a model of transactional analysis identifies descriptors of interpersonal communication that helps employees improve their responses. Hence, to provide a clear training need assessment, the dimensions of service quality and descriptors of functional fluency must be mapped accordingly. Design/methodology/approach: The semantic mapping of the dimensions of the service quality with descriptors of the functional fluency model. Findings: Out of the five dimensions of the SERVAQUAL model, four being behavioral are mapped with four descriptors belonging to four different modes of the functional fluency model. The four modes are positive manner in which people can respond to improve service quality. Research limitations/implications: The implication is the training needs that emerge by bridging the gap between SERVQUAL dimensions and functional fluency model for self-development. Practical implications: This will provide an organization the training needs analysis for their employees for improving their interpersonal communication on service quality dimensions. Originality/value: Bridging of the gap between customer's assessment of service quality dimensions (SERVQUAL model) and the descriptors of training (Functional Fluency model).